A Novel Building Performance Based Climate Zoning for Ethiopia - Zeleke, Belay; Kumar, Manoj; Rajasekar, E. (Frontiers in Sustainable Cities, 2022)
Climate zoning plays a vital role in the development and implementation of building energy regulations. This paper presents a novel building performance-based approach for climate zoning. By using a high resolution spatial climate dataset, a climate severity mapping of Ethiopia is presented. Ethiopia represents 13 of the Köppen Geiger global climate zones. Real-time thermal performance measurement of representative residential buildings in three climatic locations is presented. Thermodynamic models of these buildings are developed and validated using energyplus software tool. Hourly building simulations of these buildings are performed for 1490 locations (15 minutes spatial resolution) across Ethiopia. Cooling and heating discomfort hours, as well as energy performance index, are computed for each of these geolocations. Spatially interpolated building performance metrics and adaptive thermal comfort limits are presented. The relevance of Köppen Geiger's classification in the context of building performance is statistically tested. We observed that the existing climate zones do not considerably represent the building thermal performance and energy footprint. The effect of thermal severity on building performance is described. Further, climate zones are deduced based on the building performance variables using multivariate statistical clustering. In order to evaluate potential climate responsive strategies, the bioclimatic zoning of Ethiopia is presented. The bioclimatic zoning is created using an improved Mahoney’s method that incorporates solar radiation. This analysis resulted in 21 bioclimatic strategy zones. A comparative assessment of the new climate zoning with Mahoney’s bioclimatic classification is presented. The proposed framework will be relevant for regulating building performance and energy conservation measures.